Working Capital: Development of the Field through Scientific Mapping: An Updated Review - Ángel-Sabino Mirón Sanguino; Eva Crespo-Cebada; Elena Muñoz Muñoz; Carlos Diaz Caro (Administrative Sciences, 2024)
Throughout history, the analysis of companies’ financial structure has been approached from different angles, with different areas of the overall financial situation being separated and studied independently in order to improve understanding. Within the framework of short-cycle analysis and, more specifically, of the cash flow statement, it is of vital importance for a company to manage an adequate proportion of working capital, and this is where the focus of the present work is centred. This study was carried out to offer support to the theoretical framework for future research on working capital, given its importance for the analysis of the operational cycle of companies. This study uses bibliometric techniques to gain a better understanding of the current situation and trends in this area of research. The results are framed in all of the periods in which work on working capital has been documented, which are divided into two periods: up to 2019, and from 2020 to 2024. The results show the current evolution of the topics, with supplier credit dominating, and indicate potential topics for further research to address in this area.